(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, school, university, and vocational school pupils and students are given an understanding of modern psychology. The structure of modern psychology, its main branches.You will have information about the methods of scientific investigation of psychology .